Safety analysis of electromagnetic wave energy received by underground columnar metal structures - Sihan FAN; Wei YANG; Zijian TIAN (Meitan kexue jishu)
In the narrow space underground, it is necessary to install brackets, lighting lines, steel rails, coal trucks and air doors, resulting in the concentration of metal structures underground. Underground metal structures may receive electromagnetic wave energy from transmitting antennas through magnetic coupling or receiving radiated electromagnetic waves. If there are breakpoints in the metal structure, an induced voltage can be generated at the breakpoint. If there is scraping at the breakpoint of the metal structure, it will generate scraping discharge sparks at a very low voltage in the form of scraping discharge at the breakpoint, which poses a risk of igniting and detonating gas. In order to avoid gas explosion accidents caused by metal structures receiving electromagnetic wave energy from transmitting antennas as much as possible, and to ensure mine safety, it is of great significance to study the safety of electromagnetic wave energy on underground gas. In previous studies, the forms of underground metal structures were not subdivided, such as columnar metal structures and circular metal structures. The form of metal structures has a significant impact on receiving electromagnetic wave energy. Therefore, this article analyzes the safety of electromagnetic wave energy of underground columnar metal structures, and studies the safety of equating underground columnar metal structures to dipole receiving antennas to receive electromagnetic wave energy. By establishing an equivalent dipole receiving antenna circuit of a columnar metal structure, the power consumption of the load corresponding to the scratch discharge spark generated at the breakpoint of the columnar metal structure was calculated. The impact of frequency and load matching issues on power consumption of the load was analyzed, and the maximum power consumption of the load was determined, as well as the safe distance that should be maintained between the equivalent dipole receiving antenna of a columnar metal structure and the transmitting antenna. The effects of the arm length and radius of the equivalent dipole receiving antenna of a columnar metal structure, as well as the angle between the equivalent dipole receiving antenna and the transmitting antenna, on the maximum power consumption of the load and the safe distance are simulated. The simulation results show that the safe distance increases with the increase of the arm length and radius of the equivalent dipole receiving antenna of the columnar metal structure, and decreases with the increase of the angle.